2018
DOI: 10.1016/j.ijbiomac.2017.08.083
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of cassava starch films incorporated with blueberry pomace

Abstract: This work is focused on the development of renewable and biodegradable films by the valorisation of wastes from food processing industries, with the aim of contributing to the development of more sustainable films. In this context, different contents of blueberry pomace (BP) were incorporated into cassava starch (CS) film forming solutions and the functional properties of the films prepared by solution casting were investigated, specifically, thermal, optical and physicochemical properties. BP-incorporated fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
85
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 36 publications
14
85
3
3
Order By: Relevance
“…These findings are in agreement with previous studies by Ribeiro, in which an anionic polysaccharide significantly improved the quality of strawberries. In fact, we believed that edible coatings prepared with polysaccharides, particularly starches and its derivation, contained several good film‐forming composites and exhibited low oxygen permeability, which reduced the respiration rate of fresh products …”
Section: Resultsmentioning
confidence: 99%
“…These findings are in agreement with previous studies by Ribeiro, in which an anionic polysaccharide significantly improved the quality of strawberries. In fact, we believed that edible coatings prepared with polysaccharides, particularly starches and its derivation, contained several good film‐forming composites and exhibited low oxygen permeability, which reduced the respiration rate of fresh products …”
Section: Resultsmentioning
confidence: 99%
“…Luchese et al [35] used blueberry powder, corn starch, and glycerol to produce the bioplastic films by casting and concluded that the film could be used for food packaging or even for sensing food deterioration. Song et al [36] prepared biodegradable films, using diverse concentrations of lemon essential oil plus surfactants into corn and wheat starch film and described the microstructure, antimicrobial, and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Once the process is complete, the filmogenic solution (film-forming solution) was cooled to 60 • C and emptied immediately in polystyrene Petri dishes (Ø = 15 cm) using 40 g/box. Boxes with the filmogenic solutions were dried under laboratory condition (RH ≈ 45% ± 5% and 25 ± 1 • C) until the formed film was peeled off easily from the plate (≈ 72 h) [24,39]. Subsequently, the films were conditioned for 48 h in desiccators containing a saturated salt solution of NaBr (RH = 55% ± 5%).…”
Section: Preparation Of Coating Solutions and Filmsmentioning
confidence: 99%